ANALISIS RESIKO USAHA INDUSTRI TEMPE DI KOTA SURAKARTA - Agung Prasetyo; fivyn Dyah Ayu Permata Sari; Eko Hartoyo (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
Tempe cannot be separated from the daily consumption habits of people in Java. The raw material for the soybean tempe industry in Surakarta has imported soybeans because Surakarta was not a soybean-producing area. This study aims to know the risks of the soybean tempe industry in Surakarta City. The method of determining the area was done by purposive sampling. The data used are primary and secondary data. Data collection techniques were carried out by observation, interviews, and data recording. The results showed that the average total cost incurred by the tempe industry entrepreneurs per month was Rp. 18,222,146. The average revenue earned in one month is Rp. 29,474,038, so it can be seen that the average profit earned is Rp. 11,251,892. Tempe industrial business has high risk with the coefficient of variation obtained of 2.09, the coefficient of variation obtained is greater than the standard coefficient of variation of 0.5. The lower limit of this industry's profit was negative Rp. 35,729,041.54, so that the tempe industry entrepreneurs are at risk with a possible loss per month of Rp. 35,729,041.54. Administrative efforts are needed in the bookkeeping of the tempe industry and additional income from the sale of waste and tempe product innovation